Beyond the usual suspects: contrasting perspectives of developers and peripheral users of model-based energy scenarios - Yann Blumer; Devon Wemyss; Lukas Braunreiter (Environmental Research: Energy)
Model-based energy scenarios promise to provide reliable, science-based decision support to societal actors. However, these scenarios do not always sufficiently address the information needs of a scenario user. This study aims to better understand this gap with a focus on peripheral users—such as local authorities and regional energy companies—who are often overlooked in scenario development yet play a crucial role in shaping the future energy system through their aggregate decisions. The study surveyed academic energy modelers ( n = 105) and non-academic peripheral users ( n = 244) in Switzerland to contrast their views on the scope, purpose, and underlying epistemology of model-based energy scenarios. While both modelers and users agree on the relevance and authority of model-based energy scenarios for identifying feasible transition pathways, users are more emphatic about integrating a broad set of social dynamics into models, while modelers tend to be more selective. Further, users express more ambitious expectations concerning the purpose and scope of the entire modeling and scenario development process. This includes the expectation that scenarios come with an indication of specific probabilities, explore radically different futures, and more explicitly communicate key underlying assumptions. Overall, the study enables a direct comparison of modelers’ and users’ perspectives, using statistical inference to extend previous research and confirm the widespread acceptance of scenarios as decision-support tools. However, further work is needed to systematically understand the needs and perspectives of different users in order to realize the potential of model-based energy scenarios in aligning academia, policy, and society towards a sustainable, feasible and secure transition of the energy system.